2020
DOI: 10.1534/g3.120.401038
|View full text |Cite
|
Sign up to set email alerts
|

RhoBTB Proteins Regulate the Hippo Pathway by Antagonizing Ubiquitination of LKB1

Abstract: The Hippo pathway regulates growth and apoptosis. We identify RhoBTB proteins as novel regulators of Hippo signaling. RhoBTB depletion in the Drosophila wing disc epithelium cooperated with Yki to drive hyperplasia into neoplasia. Depletion of RhoBTB2 caused elevated YAP activity in human cells. RhoBTB2 deficiency resulted in increased colony formation in assays for anchorage-independent growth. We provide evidence that RhoBTBs acts on Hippo signaling through regulation of the kinase LKB1. LKB1 protein levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…RhoBTB1 is a tumor suppressor gene involved in different types of cancer [7,90], but its role in cardiac pathologies is still unclear. Interestingly, a recent study also suggested a regulatory role of RhoBTB on the Hippo signaling [98]. This role was reported in Drosophila and human (HEK293T) cells and was shown to be mediated by ubiquitination-dependent regulation of LKB1 kinase [151].…”
Section: Micrornas As Targets For Cardiomyocyte Proliferationmentioning
confidence: 78%
“…RhoBTB1 is a tumor suppressor gene involved in different types of cancer [7,90], but its role in cardiac pathologies is still unclear. Interestingly, a recent study also suggested a regulatory role of RhoBTB on the Hippo signaling [98]. This role was reported in Drosophila and human (HEK293T) cells and was shown to be mediated by ubiquitination-dependent regulation of LKB1 kinase [151].…”
Section: Micrornas As Targets For Cardiomyocyte Proliferationmentioning
confidence: 78%
“…Genes encoding RhoBTB proteins exhibit ubiquitous but tissue-differential expression ( Berthold et al, 2008b ; Ji and Rivero, 2016 ; Nguyen et al, 2020 ). RhoBTB1 and RhoBTB2 have been regarded as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…RhoBTB1 and RhoBTB2 are highly similar, whereas RhoBTB3 is the most divergent member ( Aspenström et al, 2004 ; 2007 ; Berthold et al, 2008b ; Espinosa et al, 2009 ). Interestingly, the RhoGTPase domain of RhoBTB3 binds and hydrolyses ATP, whereas that of RhoBTB1/2 binds GTP ( Aspenström et al, 2004 ; 2007 ; Berthold et al, 2008a ; Nguyen et al, 2020 ). Moreover, only RhoBTB3 bears an isoprenylation CAAX motif that is typical of classical RhoGTPases in the C-terminal region ( Ji and Rivero, 2016 ; Junaid et al, 2014 ; Manolaridis et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two SMGs from our analysis (LATS1 and NF2) are core members of the HIPPO signalling pathway, while SMGs FAT1, JUB and STK11 are known regulators of HIPPO signalling [21][22][23] . Mutations in LATS1, FAT1, JUB, STK11 or NF2 (the latter two of which are signi cantly mutated speci cally in C2 tumours, Fig.…”
Section: C2 Tumours Display Hippo Pathway Alterations and Increased Yap1 Activitymentioning
confidence: 99%